The influence of cultural practices and socioeconomic factors on teenage pregnancy across selected primary health care centers in Akinyele local government area, Ibadan, Nigeria - Shimilimo, Agness; Amos, Makelele M.; Million, Solomon T.; Courage, Chandipwisa; Adesina, Oladukun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Teenage pregnancy is a significant contributor to maternal and child mortality and a driver of the cycle of ill health and poverty, particularly in low- and middle-income countries (LMICs). Globally, around 21 million girls aged 15-19 and 2 million under 14 give birth annually, with 95% of these births occurring in developing countries. In Nigeria, the burden of teenage pregnancy is exacerbated by cultural practices, socioeconomic challenges, and limited access to education and reproductive health services. Methods: A cross-sectional study was conducted across selected primary health care (PHC) centers in Akinyele local government area (LGA), Ibadan, Nigeria. Twelve PHCs were randomly selected, one from each ward. A multi-stage sampling method was used to select teenage antenatal attendees. A sampling frame was developed from antenatal records, and eligible participants were chosen using computer-generated random numbers. Data were collected using a validated questionnaire with both open- and close-ended questions from July to August 2024. Statistical analysis was done using IBM SPSS version 27.0, with significance set at p≤0.05. Results: Peer pressure (58.5%) and family pressure (46.5%) were the most reported causes of teenage pregnancy. Cultural barriers around sex education and contraception were reported by 80.3% of participants, with only 9.4% affirming open dialogue. Financial hardship and lack of educational opportunities were also cited by 78.7% as key contributing factors. The mean age of respondents was 17.5 years (SD±1.57). Conclusions: Cultural and socioeconomic factors significantly influence teenage pregnancy, highlighting the urgent need for targeted interventions in education, family engagement, and reproductive health communication.